2013
DOI: 10.1007/s00247-013-2794-y
|View full text |Cite
|
Sign up to set email alerts
|

Greater saphenous venous access as an alternative in children

Abstract: In children, the greater saphenous vein provides a safe, suitable alternative for venous access, particularly in very young children (<10 kg) and in a select group of older children who are not mobile. In the lower extremities, greater saphenous venous puncture and access may be a preferred initial access site in small children to preserve future venous access.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…The absence of complications related to the puncture technique in these five reports showed that the SVMS is a safe alternative for venous access in infants and/or bedridden children and is in agreement with the results of a previous study (15) that used the saphenous vein in 86 children with a mean weight of 9.98 kg, 81 children aged less than 2 years. No immediate complications occurred after catheter insertion and the median catheter stay was 15.8 (2-97) days.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The absence of complications related to the puncture technique in these five reports showed that the SVMS is a safe alternative for venous access in infants and/or bedridden children and is in agreement with the results of a previous study (15) that used the saphenous vein in 86 children with a mean weight of 9.98 kg, 81 children aged less than 2 years. No immediate complications occurred after catheter insertion and the median catheter stay was 15.8 (2-97) days.…”
Section: Discussionsupporting
confidence: 90%
“…Another important piece of information was the anatomical location of the PICC tip after insertion, which was released for use after confirming the tip on chest radiography between T9 and T11 and/or the ideal position of the catheter tip in the distal inferior vena cava at the level of the diaphragm [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…105,106 To facilitate a rapid approach to vascular access in critically ill infants and children, the American Heart Association and the American Academy of Pediatrics developed neonatal resuscitation program (NRP) and pediatric advanced life support (PALS) guidelines for emergency establishment of intravascular support. [107][108][109][110] Essential age-specific differences include use of umbilical artery (UAC) and umbilical venous (UVC) access in newborns, and rapid use of intraosseous (IO) access in children. Ultrasound guidance facilitates placement of central lines in children, but is technologist dependent.…”
Section: Intravascular Accessmentioning
confidence: 99%
“…2,3 Vein access is an issue when these patients need medium-to long-term infusion therapy. PICC is suitable for mediumto long-term infusion therapy, which was inspired from the PICC insertion through the great saphenous vein in an infant 1,4 and the study of Zone Insertion Method. 5 Thus, we selected superficial femoral vein at the mid-thigh as the insertion site and inserted 121 femoral inserted central catheters (FICCs) via the superficial femoral vein at the mid-thigh since August 2017.…”
Section: Introductionmentioning
confidence: 99%